ISLAMIC ECONOMICS PRINCIPLES AND THEIR IMPLEMENTATION IN HOSPITAL FINANCE (CASE STUDY IN THE BRANCH HOSPITAL OF SITI KHODIJAH MUHAMMADIYAH SEPANJANG SIDOARJO) - Novian Abdi Firdausi; Sri Herianingrum (Universitas Airlangga, 2020)
This research aims to determine the implementations of Islamic economic principles in financial aspects at Siti Khodijah Muhammadiyah Sepanjang Branch Sidoarjo Hospital. Adiwarman Karim formulated five Islamic economics principles, namely Tauhid (Faith), ‘Adl (Justice), Nubuwwah (Prophethood), Khilafah (Governance), and Ma’ad (Return). Using a descriptive qualitative case study as a research approach while using in-depth interviews with key informants, and Analytic Network Process (ANP) to find which principles implementations are dominant. The Study results show that Siti Khodijah Muhammadiyah Sepanjang Branch Sidoarjo Hospital has not used a full sharia-compliant financial system yet. It has distinctive accounting guidelines, incomes and capitals purely from operating profits, and having special council as sharia supervisor. From ANP analysis, the dominant aspects are Financial Allocation from ‘Adl aspect, Leadership Management from Khilafah aspect, ZISWAF Management from Ma’ad aspect, Amanah from Nubuwwah aspect, and Akidah and Akhlak from Tauhid aspect.Keywords: Islamic economic principles, hospital finance, implementation, ANPREFFERENCE Amiruddin dan Abdul Aziz. (2017). Secularism in medicine from maqasid al-syariah. International Journal of Academic Research in Business and Social Sciences, 7(12), 613-623. doi:10.6007/IJARBSS/v7-i12/3643Effendi, Jaenal. (2018). Islamic insurance: a potential niche market of Indonesia. Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 10(1), 207-230. doi:https://doi.org/10.15408/aiq.v10i1.5330Gapenski, Louis C. (2009). Fundamentals of Healthcare Finance. Chicago: American College of Healthcare Executives.Hasan, Zubair. (2016). Evolution of Islamic economics: definition, nature, methodology, problems and challenges. ISRA International Journal of Islamic Finance, 8(2), 9-25.Idri dan Rohaizan Baru. (2017). The principles of Islamic economics and their implementation in Indonesia. International Journal of Academic Research in Business and Social Sciences, 7(4), 331-344. doi: 10.6007/IJARBSS/v7-i4/2809Karim, Adiwarman. (2015). Ekonomi mikro Islami. Jakarta: PT Raja Grafindo Pustaka.Liao, Sen-Kuei dan Kuei-Lun Chang. (2009). Measure performance of hospitals using analytic network process (ANP). International Journal Business Performance and Supply Chain Modelling, 1(2/3). 129-143. doi: 10.1504/IJBPSCM.2009.030638Mahjom, Haji Alias dan Zulkifli. (2011). Critical success factors for bumiputera/muslim medical tourism providers: solution for financing needs using Islamic financing instruments. Prosiding PERKEM VI Jilid 2.Moleong, Lexy. (2017). Metodologi penelitian kualitatif. Bandung: Remaja Rosdakarya Offset.Muhamad. (2014). Manajemen keuangan syari’ah: analisis fiqh & keuangan. Yogyakarta: UPP STIM YKPN.Rahimi dkk. (2014). Indicators of hospital performance evaluation: a systematic review”. International Journal of Hospital Research, 3(4), 199-208.Rahman, Zailani dan Musa. (2017). The perceived role of Islamic medical care practice in hospital: the medical doctor perspective. Journal of Islamic Marketing, 9(1), 00-00. doi: 10.1108/JIMA-01-2016-0006Razak dan Abdulahi. (2016). Incorporating moral values and maqasid al-syari’ah into medical and healthcare practices. The International Medical Journal of Malaysia, 15(2), 1-2.Rozalinda. (2015). Ekonomi Islam: teori dan aplikasinya. Jakarta: Rajawali Press.Saaty dan Vargas. (2006). Decision making with the analytic network process economic, political, social and technological applications with benefits, opportunities, costs and risks. New York: Springer Science+Business Media.Shariff dan Rahman. (2016). Shari’ah compliant hospital; from concept to reality: a Malaysian experience. Bangladesh Journal of Medical Science, 15(1), 1-4.Sulistiadi dan Rahayu. (2017). Assessment of first sharia hospital certification in Indonesia facing the global competition. Batusangkar International Conference II 14-15 October 2017.Talaat, dkk. (2016). an-nur specialist hospital: islamic management practices. The International Journal of Business & Management, 4(11). 116-122.Trisnantoro, Laksono. (2015). Memahami penggunaan ilmu ekonomi dalam manajemen rumah sakit. Yogyakarta: Gadjah Mada University Press.Yin, Robert K. (2015). Studi kasus: desain & metode. Jakarta: Rajawali Press.Yuana, Nurvita Risa. (2015). Tinjauan ekonomi Islam terhadap kualitas jasa pelayanan kesehatan bagi pasien kelas III (studi kasus rumah sakit umum daerah Arifin Achmad Pekanbaru). Skripsi tidak diterbitkan. Pekanbaru: UIN Sultan Syarif Kasim Riau.